No Association between Elevated Thyroid-Stimulating Hormone at Birth and Parent-Reported Problem Behavior at Preschool Age - Trumpff, Caroline; De Schepper, Jean; Vanderfaeillie, Johan; Vercruysse, Nathalie; Tafforeau, Jean; Van Oyen, Herman; Vandevijvere, Stefanie (Frontiers in Endocrinology, 2016)
Objectives: Mild level of iodine deficiency during pregnancy may reduce maternal thyroid hormone production and supply to the fetus hence affecting brain neurodevelopment. The aim of the present study was to investigate the association between elevated neonatal thyroid stimulating hormone (TSH) level (>5 mU/L), used as a marker of maternal mild iodine deficiency during late pregnancy, and behavioral development of preschool children. Methods: This retrospective cohort study included 310 Belgian mothers and their children aged 4-5 years old with TSH levels in the range of 0.45-15 mU/L at birth. The TSH level was measured in dried blood spots on filter paper collected by heel stick three to five days after birth. Low birth weight, prematurely born children or children with congenital hypothyroidism were excluded. The degree of behavioral problems was evaluated using the Child Behavior Check List (CBCL) for age 1½ to 5 Years questionnaire. Relevant socioeconomic, maternal and child factors were also collected. Results: TSH concentrations and CBCL scores were not associated both in univariate analysis and when adjusting for confounding factors in multivariate analysis. Discussion: Elevated TSH concentrations measured at birth was not associated with behavioral development scores.